Students' perceptions of the implementation of the Institutional Integrated Curriculum Articulation System (SAICI) at the Faculty of Administrative, Economic, and Accounting Sciences (FACAEC) of the Unidad Central del Valle del Cauca (UCEVA) (2024)
ilustraciones, gráficos, tablas